2011
DOI: 10.1007/s00167-011-1483-3
|View full text |Cite
|
Sign up to set email alerts
|

Computer-assisted gap balancing technique improves outcome in total knee arthroplasty, compared with conventional measured resection technique

Abstract: Computer-assisted gap balancing technique was able to achieve more precise soft tissue balance and restoration of limb alignment with better knee scores as compared to the conventional measured resection technique in total knee arthroplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
96
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(98 citation statements)
references
References 45 publications
2
96
0
Order By: Relevance
“…Other studies report revision rates of navigated TKAs: Hernández-Vaquero et al assessed 100 patients with a follow-up of eight years and detected similar revision rates between conventional and navigated techniques [18]. Harvie et al evaluated 71 patients and found no revisions after five years [19], Pang et al 140 patients and no revisions after two years [20], and Ishida 54 patients and one revision in each group after five years [21]. Lüring et al performed a matched-pair analysis of 100 patients and detected no revision after five to seven years [22].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies report revision rates of navigated TKAs: Hernández-Vaquero et al assessed 100 patients with a follow-up of eight years and detected similar revision rates between conventional and navigated techniques [18]. Harvie et al evaluated 71 patients and found no revisions after five years [19], Pang et al 140 patients and no revisions after two years [20], and Ishida 54 patients and one revision in each group after five years [21]. Lüring et al performed a matched-pair analysis of 100 patients and detected no revision after five to seven years [22].…”
Section: Discussionmentioning
confidence: 99%
“…Another difficulty with patient-specific guides is that they do not take into account the effects of soft tissue balancing. The gap-balancing technique has been advocated over the measured resection technique in some studies, including navigation studies, in terms of less abnormal femoral component rotation and coronal instability and better functional outcome [8,10,17,24]. We used the gravity traction method, which uses gravity as a tension force for reproducing a rectangular flexion gap.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, a decreased joint gap value during 90°to 135°of knee flexion showed an inverse correlation with the postoperative knee flexion angle because a larger tightness of the extensor mechanism including the PF joint leads to a poorer knee flexion angle [10]. On the other hand, other reports have concluded that there is no significant clinical difference between gap balancing technique and conventional measured resection technique [18,28]. In the future, further research on the relationship between gap asymmetry in UKA using spacer block technique and range of motion and clinical results should be conducted.…”
Section: Discussionmentioning
confidence: 88%